THE IMPLEMENTATION OF CONSENSUAL REGULATORY MECHANISM FOR ACTIVITIES OF FOREIGN DIRECT INVESTORS IN AFRICA - D. Fogel (Вестник университета)
The article covers the issues of institutional changes in the African mechanism for attraction of foreign direct investments (FDI). African nations are trying to attract FDI in greater volume and to assure that such capital serves the purposes of economic development, including creation of jobs, reduction of poverty and mobilization of local capital and other factors of production. As the results of the research state, that it is productive for foreign enterprises, including Russian entities, to apply consensual approach in epistemology studies of African investments codes. Such methodology can concurrently assure the profitability of business and improvements of economic situation in host African economies.